The Role of Entrepreneurial Marketing and Digital Engagement on Innovative Work Behavior in Tourism MSMEs, Moderated by Social Media Algorithms - Dinda Amalia Amalia; Willy Adi Cahya; Djeimy Kusnaman; Oki Anggraeni; Yulia Nur Hasanah (Universitas Tidar, 2025)
This study investigates how entrepreneurial marketing and digital engagement influence innovative work behavior in Indonesian tourism MSMEs, while also examining the moderating role of social media algorithms. Drawing on the Resource-Based View, the study conceptualizes entrepreneurial marketing and digital engagement as critical intangible resources that potentially drive firm-level innovation. Employing Partial Least Squares Structural Equation Modeling with data from tourism MSMEs, the findings reveal that digital engagement significantly enhances innovative work behavior, whereas entrepreneurial marketing shows a marginally significant impact. Contrary to expectations, the moderating effects of social media algorithms were not statistically significant, indicating these external digital dynamics may not meaningfully shape the resource-innovation linkages. These insights extend theoretical discussions by emphasizing the differentiated contributions of internal capabilities and the limited moderating role of external algorithmic factors. Practically, the study highlights the necessity for MSME managers to invest in robust digital engagement strategies to cultivate innovation. Future research could explore additional moderating variables or adopt cross-industry perspectives to enrich the understanding of innovation dynamics in small enterprises. This research thus provides both theoretical and practical contributions, underscoring how internal digital competencies predominantly drive innovative behaviors within the context of Indonesia’s evolving tourism sector.